PENILAIAN KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN PERHITUNGAN ANALISIS RASIO KEUANGAN(STUDI PADA PT HANJAYA MANDALA SAMPOERNA TBK YANG TERDAFTAR DI BEI PERIODE 2011-2014) - MUSAHADAH, NAIMATUL (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACT Rate company's financial performance is very necessary because it is used as a measurement basis for investors to invest their shares, which can be done by using a calculation of financial ratio analysis through the financial statements. includes the calculation of the liquidity ratio, debt ratio, activity ratio, and profitability ratio. This reseacrh was conducted to assess the financial performance of PT Hanjaya Mandala Sampoerna Tbk, during the period 2011-2014 using quantitative descriptive method. The calculations show that PT Hanjaya Mandala Sampoerna Tbk in a liquid state being able to pay its short-term liabilities due to value ratio is obtained an average of 1.7 or> 1, but the PT Hanjaya Mandala Sampoerna Tbk is still not good because 0.97% of funding comes from debt. Activity ratio shows that PT Hanjaya Mandala Sampoerna Tbk in good condition for being able to quickly turn receivables into revenue as much as 68 times, change the inventory into revenue as much as 3.5 times, and assets into revenue as much as 2.7 times, as well as obtaining a high enough level of profitability because profits obtained from sales and investments. Keywords: financial performance, financial statements, financial ratios.